Application of geographical information system for farm mechanization education and training - Razali, Mohd Hudzari; Wayayok, Aimrun; Ssomad, M.A.H.A.; M.S., Norazean (Sjournals, 2013)
Precision farming is managing each crop production input such as fertilizer, water, lime, herbicide, insecticide and seed on a site-specific basis to reduce waste, increase profit and maintain the quality of the environment. Without some remarkable enabling assisting technologies, the individual treatment of each plant is impossible and the concept of precision farming would not be feasible. Based on the trip, we can gain more information about the new technology that applies nowadays in agriculture. By using remote sensing that transmitted data from GPS, we can used to determination of generic object type, character and property as well as it’s abstract meaning. Besides, the application of remote sensing has been used in soil electrical conductivity sensor which used for show the variability of soil properties in detail and rapidly using simple equipment with less cost and labor force. Action maps will then be produced for farmers to apply fertilizers at different rates according to the delineated zones.